Cover crops and sustainable agriculture - Islam, Rafiq, 1960-; Sherman, Bradford (Boca Raton : CRC Press, 2021)
"This book may not be known as the "encyclopedia of cover crop management," but its close. The economic and environmental benefits of individual cover crops and blends/mixes for specific agronomic crop rotations and geographic locations are included. Photos and illustrations show how cover crops look in the field, both above and below ground. The book includes details on the "hows" for successful cover cropping: how to choose cover crops for specific situations; how to plant; and how to terminate. As part of a continuous no-till system, cover crops provide long-term soil benefits and an economic return through higher yields"--
OCLC-licensed vendor bibliographic record.
Keywords: Cover crops; Sustainable agriculture; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / General; TECHNOLOGY / Agriculture / General